Pembuatan prototipe penentu kesegaran ikan patin Berbasis sensor TCS 230 - Catur Pramono Adi; Tina Fransiskha C.P.; Pola Panjaitan; Yuda Herdiansyah (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
The prototype to determine the freshness of catfish is a test tool to determine the level of freshness of catfish based on the color level of the meat in the form of R, G, B (Red, Green, and Blue) values. Making the prototype requires an Arduino Atmega 2560 which functions as the brain of all components, the TCS 230 sensor which functions to detect colors based on red, green, and blue values, then a 20×4 LCD which functions as a display of detection results. The cube-shaped chassis is made of lightweight iron and the board is water-resistant and easy to clean. This prototype has dimensions of length 28 cm, width 25 cm, and height 18 cm. In the way it works, the catfish is inserted into the cube where the TCS 230 sensor is attached which will then detect the color of the meat which is then converted into R, G, B values. The Arduino clarifies the sensor readings which are then forwarded to the LCD as the output of the test results. Based on the results of data confusion matrix testing, this prototype has a data accuracy value of 80%, a positive precision level of 83%, and a negative precision level of 67%. The results of testing the prototype freshness of catfish resulted in a success percentage of 84.4%.